A MODEL FOR ELDERLY WELL-BEING: SAENSUK’S SMART CITY SOLUTIONS - Butsabong, Chonnakan; Ritcharoen, Kanyaphon (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study investigates the role of advanced technologies in enhancing the quality of life and addressing demographic challenges through the development of Smart Cities, with a particular focus on elderly care. Method: Using a qualitative research design, the study employs field observations and case analysis of Saensuk Municipality, Thailand’s pioneering Smart City initiative that integrates technology to support aging populations. The implementation includes wearable alert devices, emergency response units, environmental hazard detection systems, and real-time incident management applications. Results: The findings reveal that the integration of these technologies significantly improves the safety, responsiveness, and overall well-being of elderly residents, transforming Saensuk into a safer and more adaptive urban environment. The study demonstrates how technology can be strategically aligned with social needs to foster inclusive urban development. Novelty: This research contributes to the global Smart City discourse by presenting a unique case of elderly-centered innovation, positioning Saensuk Municipality as a benchmark for future urban planning models that prioritize demographic inclusivity and sustainability.